The effect of fertigation on yield and quality of four white cabbage (Brassica oleracea var. capitata L.) cultivars - Nina KACJAN-MARŠIĆ; Jože OSVALD (Acta Agriculturae Slovenica)
The influence of fertigation and broadcast mineral fertilization on yield and quality of 4 cabbage cultivars (Brassica oleracea var. capitata L.) was studied in a field trial in Ljubljana. Five treatments were formed: K – classical fertilization with 150 kg N ha-1 (broadcast incorporated); FNPK – all nutrients (NPK) were applied via fertigation;  FN – P, K were added by classical methods and total N by fertigation; FNPK/30% - 30% of total N was incorporated before transplanting, total P and K and remaining N were applied via fertigation; FN/30% - total P and K and 30% of total N were incorporated before transplanting, the remainig N was applied via fertigation. During the harvest, the height and width of the cabbage, the length of stalk, weight of head with leaves and without leaves, height and width of cleaned head, firmness of head and core length were measured and the number of external trimmed leaves was counted. The largest average marketable yield was achieved by fertigation with soluble nutrients, combined with pre-plant broadcast nitrogen incorporation, with each individual cultivar as follows: Hermes F1 (38.7 t ha-1), Parel F1 (71.1 t ha-1) and Tropicana F1 (70.7 t ha-1) and the lowest by fertigation with N, where the total amount of P and K were pre-plant broadcast incorporated, with cultivars as follows: Hermes F1 (20.9 t ha-1) and Parel F1 (50.4  ha-1)  and Tropicana F1 (63.0 t ha-1) and Fieldwinner F1 (66.1 t ha-1). The firmness of cabbage heads was also influenced by the method of nutrient application.